Letter (copy) : Senor Pascual Tomas - Citrine, Walter, 1887-1983
027-0055-001 International. WMC/WJB/DT/86. 20th October, 1939. The Rt. Hon. Viscount Halifax, K.G., G.C.S.I., G.C.I.E., Foreign Office, Downing Street, LONDON, S.W.1. Dear Lord Halifax, SENOR PASCUAL TOMAS. On the 7th of October you were good enough to write to me in regard to the above named. To-day I have received word from him that the address of his wife is as follows:- Carmen Belloque Amargos, Barrio Obrero de Ramon de Castro, 24, Valencia, Spain. I am sending this information to you as it may be useful in persuing the matter. Yours faithfully, General Secretary. 292/946/27/55